(untitled) (Veterinary Science, 2024)
The current study provides evidence of the presence of microplastics in the feces of cattle, sheep, and goats under production in Ecuador as a relevant indicator in the understanding of fragmentation processes, biodistribution mechanisms, and possible effects of contamination in the agri-food chain. A total of 300 samples of ruminant feces were analyzed in a field, observational, and cross-sectional study. Using the saturated salt solution flotation technique, 75.67% of the samples were found to be contaminated with microplastics. Statistical analyses, which included frequency distribution tables, Pearson’s Chi-Square test, Z-test, and Odds Ratio using SPSS version 26 software, showed that the type of feeding is a significant factor in the presence of microplastics in ruminant feces. In addition, an 87% increase in the reduction of microplastics in ruminant feces was observed in grazing systems compared to those receiving balanced supplemental feeding. Finally, there was an 85.3% increase in microplastics found in the feces of cattle grazing near roads. These results suggest the importance of considering the type of feed and the grazing environment when addressing microplastic contamination in the agri-food chain and its potential impact on one health systems.